Cost-Effective Hybrid Wind-Photovoltaic Generation System for Isolated Critical Loads: A Case Study - Chatterjee, Arunava; Banerjee, Bratati (Journal of Electronics and Electrical Engineering, 2023)
This study provides a technical and economic analysis of integrating a microgrid structure for power generation with wind energy and photovoltaic (PV) generation. The study mainly focuses on providing optimal generation from renewable energy sources for supplying isolated critical loads with optimized cost. Using HOMER software, a financial study of the proposed wind-PV-based microgrid is presented. A model is built with artificial neural network (ANN) to further tune the simulated economic optimization results obtained for further economic optimization and validation analysis. A reduction of about 22% in cost of energy is obtained from the ANN based optimization of system cost. This indicates that the proposed hybrid generation system is a profitable one serving localized loads in isolation with 100% renewable energy utilization. The proposed system can modelled and established in an onshore area in eastern India with optimized utilization of renewable sources for generation with minimal cost as observed.